Pengalihan Pertanggungjawaban dalam Kasus Tindak Pidana Pencucian Uang - Muh Dzaki Nouval; Boedi Prasetyo (Jurnal Hukum Lex Generalis, 2024)
The crime of money laundering, as it is known, is a crime that has certain characteristics where the criminal act is not the main criminal act but a follow-up criminal act. In its implementation, the crime of money laundering is a wealth that is placed, transferred or transferred where the wealth is a wealth obtained from the crime of buying and selling narcotics. Law No. 8/2010 on the Prevention and Eradication of Money Laundering Crime stipulates that passive actors can be held criminally liable if they fail to fulfil the obligation to report suspicious transactions stipulated in the law. The sanctions imposed aim to prevent the omission of the proceeds of crime and close the opportunity for active actors to hide the origin of illegal funds. Through an approach that covers both the perpetrator's actions and the origin of the funds, the law provides a strong basis for prosecuting passive money launderers. This is important for maintaining the integrity of the financial system, mitigating the adverse impact of serious crime, and ensuring legal justice. Law enforcement against passive money laundering offences is a strategic step in preventing the misuse of illicit funds and supporting economic and social stability.